Laser-induced diffusion of an aluminum clad in an aerospace aluminum alloy for enhanced bonding - E.C.F. Morais; S.A. Silva; R.H.M. Siqueira; S.M. Carvalho; M.S.F. Lima (Results in Surfaces and Interfaces)
AA2024-T3 AlClad alloy is an aluminum alloy that is widely used in the aerospace industry. The AlClad designation refers to the application of a pure aluminum coating on the alloy surface to improve corrosion protection. Although this alloy has satisfactory mechanical behavior and corrosion resistance for aerospace applications, the aluminum coating often wears or peels during service, exposing the substrate to a corrosive environment. The objective of this study was to improve the adhesion of the coating to the alloy substrate through fiber laser glazing, where different current values of the pumping diode were used. This treatment aims to improve the anchorage between the aluminum layer and the alloy substrate, making the structures more reliable and secure. The laser used was a continuous wave ytterbium-doped fiber laser with a wavelength of 1.07 μm, beam quality (M2) equal to 9, minimum beam diameter of 0.1 mm and displacement speed of 50 mm/s. Argon gas was used to protect the specimens and lens at a flow rate of 7 l/min. The analyses were performed using profilometry, pin-on-plate slip wear, nanoindentation, light optical microscopy, scanning electron microscopy, energy-dispersive spectroscopy, and electrochemical corrosion tests. Based on the results obtained, the objective of the study was achieved for all laser-glazed specimens when the pumping current exceeded 50 %. There was an increase in the metallurgical bonding between the coating and the substrate and a decrease in the surface roughness with increasing diode pump current. Under conditions where the laser pump current was between 50 % and 70 %, the corrosion current density values were similar to those of the material without laser glazing, which indicates that the corrosion resistance was not affected in these cases. Thus, specimens with better coating adhesion and surfaces with lower average roughness and greater hardness were obtained. Consequently, less wear was observed while maintaining a corrosion resistance similar to that of the pure aluminum layer.